(3eXaQ GdfhGH jaJM GdCHhGH (B/s - (3dWja, YHGSs ((3HZOGO (B:s (3OGQ hecJHI YOfGf WHY fTQ JhRjY,s, 2013)
(3JMJ gPG GdYfhGf GdPj jJeGgi eY TGYQjI hTYQjI QeR GdYQGb GdcHjQ eXaQ GdfhGH, UOQ ddcGJH hGdfGbO YHGS dWja cJGH LOjO Ve SHYI fUhU eSQMjI hef ChdgG LGA gPG GdYfhGf GdPj EVGaI Edi eG GcJfRg ef QhM TYQjI, GcJfR SeJg GdOQGejI GdJj CgdJg djJHhC ehbY GdUOGQI ef Hjf gPg GdfUhU, GdJj de JQ GdfhQ Ydi NTHI GdeSQM, ceG gh GdMGd eY fU (B((3eXaQ GdfhGH jaJM GdCHhGH(B)(3, aeXaQ GdfhGH TGYQ JfWhj SjQJg GdPGJjI HQeJgG Ydi MHcI hKjeI OQGejI ZjQ JbdjOjI, deKba YGfi GdCeQjf hTgO JMhdGJ hUQGYGJ eJHGjfI, cGfJ GfYcGSG ObjbG dhGbY GdYQGb GdSjGSj hGdGLJeGYj MJi gPg GddMXI, EP JYQV ddedGMbI hSLf hgQH ef GdGVWgGO hGdbeY hGdJfcjd GdPj dGReg, Edi YhGUe YOI efgG HjQhJ hOeTb heOf ChQhHjI, HYO Cf CeVi aj SLfg GdUMQGhj (B((3fbQI GdSdeGf(B) (3hQGA GdbVHGf eOI ef GdRef Ke fbd Edi SLf (B((3GdMdI(B) (3haj GdCNjQ bGe GdfhGH heLehYI ef GdSLfGA HMaQ fab ef GdRfRGfI jDOj Edi NGQL CShGQ GdSLf hHYO gQhHg GdeKjQ ef GdSLf JhGQi Yf GdCfXGQ aj HZOGO hXd eNJajG ajgG Ke JhLg Edi GdLfhH (B((3GdCghGQ(B) s
(3GdeSQMjI GdYQHjI(B.s
(3HefGSHI HZOGO YGUeI GdKbGaI GdYQHjI dYGe (B2013.s
Keywords: (3GdfhGH, eXaQ,s -- 1934-2022; (3GdeSQMjGJ GdYQHjIs -- (3bQf (B21s -- (3GdYQGbs